Tumor Microenvironment Uses a Reversible Reprogramming of Mesenchymal Stromal Cells to Mediate Pro-tumorigenic Effects - Nwabo Kamdje, Armel H.; Seke Etet, Paul F.; Simo Tagne, Richard; Vecchio, Lorella; Lukong, Kiven Erique; Krampera, Mauro (Frontiers in Cell and Developmental Biology, 2020)
After more than a decade of controversy on the role of stromal cells in the tumor microenvironment, the emerging data shed lights on pro-tumorigenic and potential anti-cancer factors, as well as on the roots of the discrepancies. We discuss the pro-tumorigenic effects of stromal cells, considering the effects of tumor drivers like hypoxia and tumor stiffness on these cells, as well as stromal cell-mediated adiposity and immunosuppression in the tumor microenvironment, and cancer initiating cells’ cellular senescence and adaptive metabolism. We summarize the emerging data supporting stromal cell therapeutic potential in cancer, we discuss the possibility to reprogram stromal cells of the tumor microenvironment for anticancer effects, and we explore some causes of discrepancies on the roles of stromal cells in cancer in the available literature.